Use of medicines by persons with disabilities in São Paulo state areas, Southeastern Brazil - Castro, Shamyr Sulyvan; Pelicioni, Americo Focesi; Cesar, Chester Luiz Galvão; Carandina, Luana; Barros, Marilisa Berti de Azevedo; Alves, Maria Cecilia Goi Porto; Goldbaum, Moisés (Revista de Saúde Pública, 2010)
OBJECTIVE: To analyze the use of medicines and the main therapeutic groups consumed by persons with physical, hearing and visual disabilities. METHODS: A cross-sectional study was performed, where data from the 2002 Inquérito Multicêntrico de Saúde no Estado de São Paulo (ISA-SP - São Paulo State Multicenter Health Survey), as well as the 2003 Inquérito de Saúde no Município de São Paulo (ISA-Capital - City of São Paulo Health Survey), Southeastern Brazil, were analyzed. Respondents who reported having disabilities were studied, according to variables that comprise the database: geographic area, gender, income, age group, ethnic group, use of medicines and types of drugs consumed. RESULTS: The percentage of use of drugs by persons with disabilities was 62.8% among the visually impaired; 60.2% among the hearing impaired; and 70.1% among the persons with physical disabilities. Individuals with physical disabilities consumed 20% more medications than non-disabled ones. Among persons with visual disabilities, the most frequently consumed drugs were diuretics, agents of the renin-angiotensin system and analgesics. Persons with hearing disabilities used more analgesics and agents of the renin-angiotensin system. Among those with physical disabilities, analgesics, antithrombotics and agents of the renin-angiotensin system were the most frequently consumed medicines. CONCLUSIONS: There was a greater use of medicines among persons with disabilities than non-disabled ones. Persons with physical disabilities were those who most consumed medicines, followed by the visually impaired and the hearing impaired.